Secondary Blepharoplasty: Correction of the High Fold - Kamol Wattanakrai (2018)
© 2016, Springer Science+Business Media New York and International Society of Aesthetic Plastic Surgery. Background: Blepharoplasty is a common aesthetic surgery performed worldwide. In Asians, too high eyelid folds after blepharoplasty cause an unsatisfactory aesthetic outcome that is difficult to correct. In this article, the authors propose surgical techniques to correct the high eyelid fold after blepharoplasty. Methods: During a 4-year period, 213 secondary blepharoplasties were performed to correct high folds. Postoperative results were reviewed, graded, and analyzed. Results: Of 213 cases of secondary blepharoplasty to correct the high eyelid fold, almost all could achieve reduction of the fold size (98.59 %). One hundred and nine cases (51.17 %), 69 cases (32.40 %), and 32 cases (15.02 %) were classified as excellent, good, and fair results, respectively. Only three cases (1.41 %) were classified as poor results. Conclusion: Secondary blepharoplasty to correct a high fold is a challenging procedure for aesthetic surgeons. Surgeons performing this operation need to have a thorough understanding of eyelid anatomy and its dynamics together with familiarity with secondary blepharoplasty to avoid any further injury to the levator muscle. The key points of this surgery are levator advancement and intervening between the levator aponeurosis and the overlying skin by in situ tissue or fat grafting. Level of Evidence V: This journal requires the authors to assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors. www.springer.com/00266.